Experimental of the Tsonos model for predicting joint behavior in reinforced concrete frames - Golias, Emmanouil; Karabini, Martha; Vlasakidou, Ioanna; Papavasileiou, Filareti; Vougioukas, Emmanouil (Technical Annals, 2024)
Pushover analysis is widely regarded as the most accurate method for determining the bearing capacity of existing structures. To achieve a realistic assessment, it is essential to consider all possible failure modes. In many existing structures, joints are often designed with minimal or no transverse reinforcement, making joint failure more likely to occur before the failure of the connected members. This study employs a well-known joint behavior simulation to examine this scenario. The pushover analysis is terminated upon detecting joint failure, as it signifies a brittle failure. Analyses are performed on typical frames using both conventional criteria and the proposed joint failure criteria. The results are presented, ranked, and discussed.